AKT1E¹⁷K Is Oncogenic in Mouse Lung and Cooperates with Chemical Carcinogens in Inducing Lung Cancer. - Donatella Malanga; Stefania Belmonte; Fabiana Colelli; Marzia Scarfò; Carmela De Marco; Duarte Mendes Oliveira; Teresa Mirante; Caterina Camastra; Monica Gagliardi; Antonia Rizzuto; Chiara Mignogna; Orlando Paciello; et al. (PLoS ONE, 2016)
The hotspot AKT1E17K mutation in the pleckstrin homology domain of AKT1 occurs in approximately 0.6-2% of human lung cancers. Recently, we have demonstrated that AKT1E17K transforms immortalized human bronchial cells. Here by use of a transgenic Cre-inducible murine strain in the wild type Rosa26 (R26) locus (R26-AKT1E17K mice) we demonstrate that AKT1E17K is a bona-fide oncogene and plays a role in the development of lung cancer in vivo. In fact, we report that mutant AKT1E17K induces bronchial and/or bronchiolar hyperplastic lesions in murine lung epithelium, which progress to frank carcinoma at very low frequency, and accelerates tumor formation induced by chemical carcinogens. In conclusion, AKT1E17K induces hyperplasia of mouse lung epithelium in vivo and cooperates with urethane to induce the fully malignant phenotype.